Queer Christianities : Lived Religion in Transgressive Forms - Talvacchia, Kathleen T.; Pettinger, Michael F.; Larrimore, Mark (New York University Press, 2014)
Queerness and Christianity, often depicted as mutually exclusive, both challenge received notions of the good and the natural. Nowhere is this challenge more visible than in the identities, faiths, and communities that queer Christians have long been creating. As Christians they have staked a claim for a Christianity that is true to their self-understandings. How do queer-identified persons understand their religious lives? And in what ways do the lived experiences of queer Christians respond to traditions and reshape them in contemporary practice? Queer Christianities integrates the perspectives of queer theory, religious studies, and Christian theology into a lively conversation-both transgressive and traditional-about the fundamental questions surrounding the lives of queer Christians. The volume contributes to the emerging scholarly discussion on queer religious experiences as lived both within communities of Christian confession, as well as outside of these established communities. Organized around traditional Christian states of life-celibacy, matrimony, and what is here provocatively conceptualized as promiscuity-this work reflects the ways in which queer Christians continually reconstruct and multiply the forms these states of life take. Queer Christianities challenges received ideas about sexuality and religion, yet remains true to Christian self-understandings that are open to further enquiry and to further queerness.